Doing Well While Doing Bad? CSR in Controversial Industry Sectors - Cai, Ye (Journal of business ethics, 2012)
In this article, we examine the empirical association between firm value and CSR engagement for firms in sinful industries, such as tobacco, gambling, and alcohol, as well as industries involved with emerging environmental, social, or ethical issues, i.e., weapon, oil, cement, and biotech. We develop and test three hypotheses, the window-dressing hypothesis, the value-enhancement hypothesis, and the value-irrelevance hypothesis. Using an extensive US sample from 1995 to 2009, we find that CSR engagement of firms in controversial industries positively affects firm value after controlling for various firm characteristics. To address the potential endogeneity problem, we further estimate a system of equations and change regression and continue to find a positive relation between CSR engagement and firm value. Our findings support the value-enhancement hypothesis and are consistent with the premise that the top management of US firms in controversial industries, in general, considers social responsibility important even though their products are harmful to human being, society, or environment.